The Associations between Family-Related Factors and Excessive Internet Use in Adolescents - Faltýnková, Anna; Blinka, Lukas; Ševčíková, Anna; Husarova, Daniela (International journal of environmental research and public health, 2020)
This study examined the relationship between Excessive Internet Use (EIU) in adolescents and their family environment, namely the family type, the family economic status, the effect of parental care, the level of parental control, the amount of parental monitoring, the quality of communication, and the time spent together. The study was based on data from an international survey, Health Behaviour in School Aged Children (HBSC), conducted in Slovakia. The sample representative for adolescents included 2547 participants (51% boys) aged 13-15. Multiple-step linear regression revealed that higher parental care and parental monitoring predicted lower EIU, while higher parental overprotection and lower socioeconomic status predicted higher EIU. The results suggest that both so-called optimal parenting (i.e., the balance of emotional warmth and protection) and the adolescent's autonomy lower the risk of EIU. Family factors explained about 14% of the variance, which suggests that aside from personal, cognitive and affective factors, a close social environment also plays an important role in adolescence EIU.
Keywords: společenská třída; Adolescent Behavior; internet; Parenting; Slovakia; rodičovství; Social Class; Slovenská republika; family factors; Adolescent; internet addiction; Internet; mladiství; lidé; Humans; adolescent internet use; excessive internet use; vztahy mezi rodiči a dětmi; chování mladistvých; parenting styles; Parent-Child Relations